"It Was as Though My Spirit Left, Like They Killed Me": The Disruptive Impact of an HIV-Positive Diagnosis among Women in the Dominican Republic. (20th May 2019) - Payán, Denise Diaz; Derose, Kathryn Pitkin; Fulcar, María Altagracia; Farías, Hugo; Palar, Kartika
An HIV diagnosis may be associated with severe emotional and psychological distress, which can contribute to delays in care or poor self-management. Few studies have explored the emotional, psychological, and psychosocial impacts of an HIV diagnosis on women in low-resource settings. We conducted in-depth interviews with 30 women living with HIV in the Dominican Republic. Interviews were audio-recorded, transcribed, and analyzed using the biographical disruption framework. Three disruption phases emerged (impacts of a diagnosis, postdiagnosis turning points, and integration). Nearly all respondents described the news as deeply distressful and feelings of depression and loss of self-worth were common. Several reported struggling with the decision to disclose—worrying about stigma. Postdiagnosis turning points consisted of a focus on survival and motherhood; social support (family members, friends, HIV community) promoted integration. The findings suggest a need for psychological resources and social support interventions to mitigate the negative impacts of an HIV diagnosis.